PENGARUH TATA KELOLA PERUSAHAAN, KEPEMILIKAN KELUARGA, KEPEMILIKAN INSTITUSIONAL, DAN KUALITAS PELAPORAN TERHADAP NILAI PERUSAHAAN - Dieva Novelia Sekar Arum; Darsono Darsono (Diponegoro Journal of Accounting, 2020)
This study aims to empirically examine the Effect of Corporate Governance, Family Ownership, Institutional Ownership, and Quality of Reporting on Firm Value with performance of the firm as control variables. The population in this study are companies in Indonesia listed on the Indonesia Stock Exchange in 2016-2018. The sample of this study consisted of 152 companies listed on the Indonesia Stock Exchange (BEI) for the year 2016-2018. The data used in this study were secondary and election data the sample uses a purposive sampling method. The analysis model uses multiple linear regression. The result of this study indicate that the Corporate Governance has a positive effect on firm value, Family ownership has no effect on firm value, Institutional Ownership has a positive effect on firm value, and Quality of Reporting has positive effect on firm value.